2014
DOI: 10.1002/pd.4495
|View full text |Cite
|
Sign up to set email alerts
|

Women's views and the impact of noninvasive prenatal testing on procedures in a managed care setting

Abstract: This prospective study demonstrates a 62% reduction in invasive prenatal procedures after NIPT testing and finds safety, accuracy, and personal beliefs key to women's decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
1
29
0
1
Order By: Relevance
“…While there is evidence that the accuracy of classification of autosomal aneuploidy by NIPT is high [Tiller et al, 2015], all professional guidelines currently require that NIPT results are confirmed with invasive testing before a pregnant woman makes a termination decision. NIPT has mainly been utilized as a screening method for women identified as high-risk (e.g., as a second-tier screening test), and it is just presently being introduced for screening of women with average-risk (e.g., as a first-tier screening test replacing current screening).…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence that the accuracy of classification of autosomal aneuploidy by NIPT is high [Tiller et al, 2015], all professional guidelines currently require that NIPT results are confirmed with invasive testing before a pregnant woman makes a termination decision. NIPT has mainly been utilized as a screening method for women identified as high-risk (e.g., as a second-tier screening test), and it is just presently being introduced for screening of women with average-risk (e.g., as a first-tier screening test replacing current screening).…”
Section: Discussionmentioning
confidence: 99%
“…This argues against the concern that cfDNA screening would increase rates of pregnancy termination and support reports of patients' perspective regarding termination choices with cfDNA. 13 Despite the strong recommendation to confirm cfDNA results prior to making an irreversible pregnancy decision, some women chose termination without diagnostic testing. [9][10][11] In our study of 114 patients with positive cfDNA, 11/56 (19.6%) of those choosing termination of a singleton pregnancy OR selective reduction of a twin pregnancy for suspected autosomal trisomy did so without prenatal confirmation of karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] While the test performance characteristics have been validated, little is known about the clinical course and outcome for patients with a positive test result. [1][2][3][4][5][6]13 Proper counseling is essential to understanding the limitations of cfDNA as a screening test. [9][10][11] All women in our study received both pre-and post-test counseling, the majority by CGCs which is critical as implementation of this technology without proper counseling can lead to misunderstanding of the focused nature of the screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the timing, sensitivity and specificity of screening tests have improved, the utilization of invasive procedures, such as amniocentesis and chorionic villus sampling, by pregnant women has declined. 55, 56, 57, 58 These welcome advances also involve an unprecedented degree of complexity that has challenged our current approaches. 30, 59 …”
Section: Non-invasive Prenatal Screening (Nips) For Fetal Aneuploidiementioning
confidence: 99%